IDENTIFICAÇÃO DE SURPRESAS MONETÁRIAS E SEUS IMPACTOS SOBRE A ESTRUTURA A TERMO DA TAXA DE JUROS - Napoleone, Rafael Andretto (2014)
The market reaction related to the changes in the benchmark interest rate is relevant for the whole economy. The knowledge of the relation between monetary policy and interest rates are extremely important, since monetary surprises, in other words, mistakes in the market regarding changes Selic rate target prediction, that can affect interest rates from different maturity or maturities, directly impacting the Financial Administration. The aim of this study was to analyze the variation of the Brazilian Term Structure of Interest Rates (ETTJ) monetary surprises when checked at the time of the decision of the Brazilian Monetary Policy Committee (Copom) on the Selic rate target. For that reason, a quantitative descriptive study, which considered 88 regular meetings of the Copom in the period from January, 2004 to December, 2013 was developed. Monetary surprises were identified through two distinct ways. The first one considered rates of DI1 corresponding to the last trade on the floor of the Copom meeting s date, and the rate of the first transaction done in the next trading session. Thus 11 monetary surprises were identified. The second form averaged rates observed in the same contracts and occasions mentioned above, and thus, 10 monetary surprises were identified. For the analysis of the relation between variations of the yield curve and monetary surprises were considered maturities of 2, 3, 6, 9, 12, 15, 18 and 24 months. As a result it was observed that monetary surprises and changes in the yield curve are directly proportional, moving on in the same direction for the two distinct forms of monetary surprises identified in this study. Furthermore, it was used in the analysis of unanimity in the decision of the Copom to test their informational content, and it was observed, as a result, a smaller variation of ETTJ when the Copom decision was unanimous. In summary, it is meant that the results of this study are in line those presented by other authors, it is possible to prove the correlation between the variation of the yield curve and monetary surprises as well as verify that the magnitude of the variations decreases throughout ETTJ, a fact that may be related to the transparency of monetary policy and national experience in term of the inflation targeting system.